2021
DOI: 10.3390/socsci10110419
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Extrinsic and Intrinsic Work Values of British Ethnic Minorities: The Roles of Demographic Background, Job Characteristics and Immigrant Generation

Abstract: Despite the increasingly diverse ethnic composition of the British labor force, there is no research investigating whether ethnic minorities have different work values from the White British demographic (White British). Using nationally representative data (2012–2013), this article fills this gap by comparing extrinsic and intrinsic work values between White British and five ethnic minorities, while distinguishing between first and second generations. The results show that both first- and second- generation mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 98 publications
(143 reference statements)
0
7
0
Order By: Relevance
“…For example, ethnicity may play a role. Indeed, in a comprehensive study, Wang and Morav (2021) found that several ethnic minority groups (i.e. Bangladeshis, Indians and Black Africans) reported stronger extrinsic work values as compared with White British study participants.…”
Section: Discussionmentioning
confidence: 98%
“…For example, ethnicity may play a role. Indeed, in a comprehensive study, Wang and Morav (2021) found that several ethnic minority groups (i.e. Bangladeshis, Indians and Black Africans) reported stronger extrinsic work values as compared with White British study participants.…”
Section: Discussionmentioning
confidence: 98%
“…No. 17 (Wang & Morav, 2021). In the present study, using the self-determination theory (Ryan & Deci, 2017) According to the CFA results for the validity and reliability of nurses' WVS, the goodness of fit of the initial model did not meet the criteria.…”
Section: Ta B L Ementioning
confidence: 59%
“…Second, this study attempted to investigate the extent to which a range of job/ workplace and demographic characteristics could mediate the ethnicity differences in job control, which, although we show that they do play some role, they do not fully account for the findings. While employer discrimination is a possible explanation of the unexplained part in job control ethnicity disparities, it is also possible that differential preferences in job control could account for some of this too (Wang & Morav, 2021a). While there is some research that attempts to reveal such patterns, it is still very limited and not always in line with the 'preferences' thesis (Brynin et al 2019;c.f.…”
Section: Heterogeneity Analysismentioning
confidence: 99%
“…In addition to differential treatment, another mechanism accounting for possible penalties is that different BAME groups tend to have more extrinsic and less intrinsic work orientations than White British (Wang & Morav, 2021a), which may feed through to job choice and so job control, for instance, by trading off job control for higher pay or security.…”
Section: Introductionmentioning
confidence: 99%